Stochastic failure modelling of total hip replacement - Galibarov, Pavel E. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2009)
Failure of total hip replacement (THR) can be a highly variable phenomenon. Many factors of a different nature may affect the outcome of this operation, e.g. loads occuring in the joint, patient geometry, implant design, genetic factors, etc. Building a predictive model for failure of a THR is a technically challenging task requiring the incorporation of many uncertainties and modelling failure long-term processes.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin.